1983
DOI: 10.2527/jas1983.5761412x
|View full text |Cite
|
Sign up to set email alerts
|

Calving Date versus Calving Interval as a Reproductive Measure in Beef Cattle

Abstract: Calving date and calving interval records obtained from the Beef Cattle Division of Pioneer Hi-Bred International, Des Moines, Iowa, were studied to determine the reproductive measure of choice when a fixed breeding season is employed. Fixed model, least-squares procedures were used to analyze 2,411 records collected on purebred Red Angus, Angus and Hereford cows during the years 1969 through 1976. Calving interval decreased .86 d and calving date was delayed .11 d for each 1-d delay in previous calving date. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 0 publications
2
55
0
3
Order By: Relevance
“…It has been generally observed that early breeding individuals in temperate zone habitats are few in number compared to the rest of the population, but have higher reproductive success compared to individuals that breed later (Perrins 1970;Bourdon and Brinks 1983;Olsson and Shine 1997;Dawson and Clark 2000). This observed pattern is consistent with patterns observed in the length of endogenous rhythms; that shorter rhythms are rare compared to longer rhythms while an intermediate rhythm length is most common (Helm and Visser 2010).…”
Section: Discussionsupporting
confidence: 77%
“…It has been generally observed that early breeding individuals in temperate zone habitats are few in number compared to the rest of the population, but have higher reproductive success compared to individuals that breed later (Perrins 1970;Bourdon and Brinks 1983;Olsson and Shine 1997;Dawson and Clark 2000). This observed pattern is consistent with patterns observed in the length of endogenous rhythms; that shorter rhythms are rare compared to longer rhythms while an intermediate rhythm length is most common (Helm and Visser 2010).…”
Section: Discussionsupporting
confidence: 77%
“…No entanto, nas raças (Bourdon & Brinks, 1983), a correlação genética do IEP 1 com IEP foi negativa em todas as raças, apesar de suas correlações fenotípicas terem todas apresentado valores iguais a 1,00. A h 2 para o período de serviço (PS) foi, em geral, muito baixa nas quatro raças estudadas, principalmente na Jafarabadi que apresentou h 2 igual a 0,0 (Tabela 1).…”
Section: Resultsunclassified
“…Several such components have been investigated as measures of female reproductive performance. In beef cattle, focus has been on calving date (Bourdon and Brinks, 1983;Buddenberg et al, 1990), or the related calving day (Ponzoni, 1992) or days to calving (Meyer et al, 1990;Johnston and Bunter, 1996;Donoghue et al, 2004a). Recently, heifer pregnancy status and the outcome of subsequent rebreeding have attracted interest (Evans et al, 1999;Doyle et al, 2000;Eler et al, 2004).…”
Section: Introductionmentioning
confidence: 99%